(untitled) (Dhaka University Journal of Science, 2023)
The financial value of money and the overall stability of an economy are significantly impacted by inflation. To investigate the effect of the COVID-19 pandemic and the Russia-Ukraine war on constant inflation rates in South and Southeast Asian countries between January 2019 and December 2022, this research utilizes monthly inflation rate data from the International Monetary Fund. Autoregressive integrated moving average modeling and prediction of inflation rates and the Bai-Perron method to estimate the structural breakdown of monthly inflation rate series are employed. Graphical methods and theoretical tests are used to diagnose the models, and the Chow test is utilized to assess structural breakdown in the monthly inflation rate series. The findings indicate that the Russia-Ukraine war since February 2022 has a more significant impact on the selected countries than the COVID-19 pandemic during January 2020 to December 2021. Dhaka Univ. J. Sci. 71(2): 169-175, 2023 (July)